Robust optimization model for micro-energy grid accounting for demand response and carbon-green certificate market transactions - Liu, Xuan; Liang, Xinhua; An, Lei; Tan, Zhongfu (Frontiers in Energy Research, 2025)
Under energy structure transformation and multi-energy complementary development, there is an urgent need to explore more efficient, clean and low-carbon integrated energy utilization. The micro-energy grid can realize the synergistic and complementary operation of electricity, thermal and cooling multi-energy systems through energy conversion and storage devices, thereby mitigating the intermittency of renewable generation and spatiotemporal imbalances in energy supply-demand. This paper develops a robust optimization model for micro-energy grids that accounts for demand response and carbon green certificate market participation. The study initially establishes demand response and carbon green certificate trading models to systematically evaluate their economic impacts on both microgrid and external energy systems. Subsequently, a deterministic operational optimization model is established for the micro-energy grid, aiming at net profit maximization. Finally, the study establishes a robust coefficient-based uncertainty set for WT and PV output fluctuations, facilitating the derivation of a robust optimization model for micro-energy grid. Case studies verify the model’s capability in addressing uncertainty-related operational challenges, maintaining reliable and economical operation of energy systems with enhanced robustness and economy.